2014
DOI: 10.1016/j.celrep.2014.02.035
|View full text |Cite
|
Sign up to set email alerts
|

Death Induced by CD95 or CD95 Ligand Elimination

Abstract: SUMMARY CD95 (Fas/APO-1), when bound by its cognate ligand CD95L, induces cells to die by apoptosis. We now show that elimination of CD95 or CD95L results in a form of cell death that is independent of caspase-8, RIPK1/MLKL, and p53, is not inhibited by Bcl-xL expression, and preferentially affects cancer cells. All tumors that formed in mouse models of low-grade serous ovarian cancer or chemically induced liver cancer with tissue specific deletion of CD95 still expressed CD95, suggesting that cancer cannot fo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

19
179
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
4
3
1

Relationship

1
7

Authors

Journals

citations
Cited by 78 publications
(198 citation statements)
references
References 21 publications
19
179
0
Order By: Relevance
“…When transfecting siCAG/CUG into various human (Fig 1B) and mouse (Fig 1C) cancer cell lines at 10 nM, all cancer cells stopped growing within hours of transfection and eventually most of the cells died with no outgrowth of recovering cells (Movies EV1-EV10) (Appendix Fig S1A). All cancer cells transfected with siCAG/CUG showed morphological changes similar to the ones we observed in cells undergoing DISE (Appendix Fig S1B, [15,17]). We found that siCAG/CUG killed HCT116 cells even when transfected at 10 pM (Fig 1D).…”
Section: Introductionsupporting
confidence: 57%
See 2 more Smart Citations
“…When transfecting siCAG/CUG into various human (Fig 1B) and mouse (Fig 1C) cancer cell lines at 10 nM, all cancer cells stopped growing within hours of transfection and eventually most of the cells died with no outgrowth of recovering cells (Movies EV1-EV10) (Appendix Fig S1A). All cancer cells transfected with siCAG/CUG showed morphological changes similar to the ones we observed in cells undergoing DISE (Appendix Fig S1B, [15,17]). We found that siCAG/CUG killed HCT116 cells even when transfected at 10 pM (Fig 1D).…”
Section: Introductionsupporting
confidence: 57%
“…DISE (death induced by survival gene elimination) was found to involve simultaneous activation of multiple cell death pathways, and cancer cells have a hard time developing resistance to this form of cell death [17]. DISE was found to preferentially affect transformed cells [17].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…We have subsequently demonstrated that when either CD95 or CD95L are eliminated cancer cells die through a process we have coined DICE (for death induced by CD95R/L elimination) 12 . DICE is a necrotic form of mitotic catastrophe characterized by cell swelling and ROS production followed by DNA damage, activation of caspase-2, and loss of mitochondrial outer membrane potential (MOMP) 12 . DICE appears to be a fundamental mechanism, since it was consistently detected in all cancer cells investigated and in an in vivo mouse model of low-grade ovarian cancer.…”
Section: Introductionmentioning
confidence: 99%
“…Upon perusing the literature, we found this to be consistent with an analysis of multiple genome-wide shRNA lethality screens conducted by the HTS Core Facility at Memorial Sloan-Kettering Cancer Center (MSKCC), which indicated that RIP1 shRNAs were selected against in 9 of 12 cancer cell lines where such screens were conducted. 6 This consistently observed negative selection of RIP1 shRNAs under normal growth conditions underscored to us the significance that the presence of RIP1 shRNAs were selected for when autophagy was artificially limited in 67NR cells (these cells require autophagy for growth) or when these cells were starved in Earle's Balanced Salt Solution (EBSS). Upon further investigation, we found that the acute knockdown of RIP1 led to a large increase in basal autophagic flux in multiple cell types.…”
Section: Basal Autophagy Is Negatively Regulated By Rip1mentioning
confidence: 99%